Đáp án:
Giải thích các bước giải:
câu 1:
a)$5x^2-3x+1$
Đặt $f(x)=5x^2-3x+1$
Ta có :
$5x^2-3x+1=0 (PtVN)$
Vậy $f(x)>0 \forall x$
b)$-2x^2+3x+5$
Đặt $f(x)=-2x^2+3x+5$
Ta có :
$-2x^2+3x+5=0\to$\(\left[ \begin{array}{l}x=\dfrac{5}{2}\\x=-1\end{array} \right.\)
BXD:
-∞ + -1 - $\dfrac{5}{2}$ + +∞
Vậy $f(x)>0,\forall x \in (-\infty;-1)\cup(\dfrac{5}{2};+\infty)$
$f(x)<0,\forall x\in (-1;\dfrac{5}{2})$
c)$(2x-3).(x+5)$
Đặt $f(x)=(2x-3).(x+5)$
Ta có :
$2x-3=0\to x=\dfrac{3}{2}$
$x+5=0\to x=-5$
BXD:
-∞ + -5 - 3/2 + +∞
Vậy $f(x)>0,\forall x \in (-\infty;-5)\cup(\dfrac{3}{2};+\infty)$
$f(x)<0,\forall x\in (-5;\dfrac{3}{2})$
3)
a)$4x^2-x+1<0$
$⇔(2x^2-\dfrac{1}{4})+\dfrac{15}{16}>0\forall x$
Vậy bpt vô nghiệm
b)$\dfrac{1}{x^2-4}<\dfrac{3}{3x^2+x-4}$
$⇔\dfrac{1}{(x-2).(x+2)}<\dfrac{3}{(x-1).(3x+4)}<0$
$⇔\dfrac{(x-1).(3x+4)-3(x-2).(x+2)}{(x-2).(x+2).(x-1).(3x+4)}<0$
$⇔\dfrac{3x^2+x-4-3x^2+12}{(x-2).(x+2).(x-1).(3x+4)}<0$
$⇔\dfrac{x+8}{(x-2).(x+2).(x-1).(3x+4)}<0$
Ta có :
$x-2=0\to x=2$
$x+2=0\to x=-2$
$x-1=0\to x=1$
$3x+4=0\to x=\dfrac{-4}{3}$
$x+8=0\to x=-8$
-∞ - -8 + -2 - -4/3 + 1 - 2 + +∞
Vậy tập nghiệm của bpt là :
$x\in (-\infty;8)\cup(-2;-4/3)\cup( 1;2)$